(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
In this article, the author reflects on uzbek national experience of improving the reading competence of elementary school students, classifying fiction and popular science books published for children in modern times from the perspective of age and interest, and describes what pedagogical knowledge and experience elementary school students should possess in attracting children to reading.